THE ANALYSIS OF CRITICAL-KEY AUDIT ISSUES IN INDEPENDENT AUDIT REPORTS OF INSURANCE COMPANIES LISTED TO THE EXCHANGE: THE EXAMPLE OF THE USA AND TURKEY (Third Sector Social Economic Review, 2023)
In order to increase the confidence in independent audit reports, the standard that requires the identification and disclosure of critical audit matters in independent audit reports has entered into force in the United States (USA). For the same purpose, BDS 701 standard has been put into practice in Turkey. As a requirement of these two standards, critical/key audit matters are required to be explained in the independent audit reports. In this study, it is purposed to compare critical and key audit matters. For this purpose, the independent audit reports of listed insurance companies in the USA and Turkey between the years 2017-2021 were examined. In the reports examined within the scope of the study, it was determined what the critical/key audit matters were determined first. Afterwards, which factors were taken into account in the determination of these matters and how the determined matters were handled during the audit process were analyzed. Content analysis method was used in the study. As a result of the analyzes made, it was seen that similar factors were taken into account in the determination of critical/key audit matters. These factors are the materiality of the matter in terms of the financial statements, significant accounting estimates involved in the subject matter, the subject requires advanced technical assessment in terms of financial reporting and the matter being based on actuarial guesswork and judgment. Contrary to the objectives of the relevant standards, it has been determined that the same and stereotyped expressions are generally used in the explanations about critical/key audit matters in the audit reports examined.
Keywords: Independent Audit; Key Audit Matters; Critical Audit Matters; Insurance Companies; ISA 701